Legal Amazon, sustainable use and environmental surveillance systems: historical legacy and future prospects - Oliveira, Eduardo Frederico Cabral de; Oliveira, Jose Francisco de; Silva, Jose Augusto Ferreira da [UNESP] (Associacao Brasileira De Engenharia Sanitaria E Ambiental, 2021)
Tropical rainforests are among the most endangered biomes on the planet. They have become the new frontiers for capital expansion, both for the production of agricultural commodities and the exploitation of their natural resources. This article seeks to analyze how the command and control system is being practiced on one of such tropical rainforests, namely the Brazilian Amazon. To achieve the objectives set in the research, exploratory/descriptive methods of qualitative and quantitative approach were carried out through field research and literature review on the subject. In addition, we evaluated the publications that best described the state of the art of the theme, always aiming at the quality and comprehensiveness of research by bibliometric mining and field survey through questionnaires administered to military police corporations. While examining the environmental protection agencies and law enforcement agencies, both from Union and the states that make up the Legal Amazon, the conclusion was that all of them devote very little material resources to effective forest protection, and that human resources are infinitely smaller than those recommended by other international nature protection organizations. Moreover, the structure in charge of investigating environmental crimes in the states is either poor or non-existent, and distant from the main regions of deforestation and other environmental crimes, something which favors impunity. It is concluded that the lack of structure of command and control bodies in the Amazon threatens the sustainability of the ecosystem, the economy and the society on local, regional, and global levels.
Keywords: military police; environmental security; environmental inspection; command and control; public policies